Implementasi Konsep Arsitektur Berkelanjutan pada Fasilitas Desa Wisata Mattabulu - Syarif - Beddu; Triyatni - Martosenjoyo; Syavir - Latif; Rahmi Amin Ishak; Dahniar - -; Teguh Iswara Suardi; Syahriana Syam (Faculty of Engineering UNHAS, 2023)
Sustainable architecture is an architectural work that adopts many materials sourced from the surrounding nature, the technical construction is easy to apply by local craftsmen and does not require specific skills. Mattabulu Village has been designated by the Soppeng Regional Government as a Tourism Village, and strengthened by the decision of the Minister of Tourism and Creative Economy, for the award as an Indonesian Tourism Village 2021. The main purpose of this service is to assist partners as managers of the Village-Owned Enterprises